# Solve 2(x-4)= 2[x-3(x-1)+2], Can You Solve And Show Solution?

In order to find out the answer of the following sum: 2(x-4) = 2[x-3(x-1) +2], you would need to break it down very slowly and in small parts, step by step, and this is the key to most mathematical equations. If you look at it as a whole, you will most probably just confuse yourself, so take one step at a time and take one part of the sum and solve it, before moving onto the next part.
Let's start by looking at the first part of the sum and then we'll go forward from there:
2x - 8 = 2(x-3x+3+2)
2x-8 = 2(-2x+5)
Followed by...
2x-8 = -4x + 10
2x+4x = 10+ 8
6x = 18
x= 18/6
After breaking this sum down into very small and manageable parts, you will find that the answer to the whole sum is:
X = 3
When you view a sum of such length, full of different characters and numbers, it can feel daunting straight away. But like anything, when it is broken down and those parts looked at separately, the task doesn't seem so bad at all.
A good site to look at is quickmathsolutions.com as this website automatically answers the most common problems in algebra, equations and calculus.
thanked the writer.
2(x-4)= 2[x-3(x-1)+2]

2x - 8 = 2(x-3x+3+2)

2x-8 = 2(-2x+5)

2x-8 = -4x + 10

2x+4x = 10+ 8

6x = 18

x= 18/6

thanked the writer.
2(x-4)=2[x-3x+3+2]
2x-8=2(-2x+5)
2x-8=-4x+10
6x=18
x=3
thanked the writer.
4-(3-x) < 3x-(3-2x)
thanked the writer.
2x-8=2{x-3x+3+2}
2x-8=2{x-3x+5}
2x-8=2x-6x+10
2x-2x+6x=10+8
6x=18
X=3
thanked the writer.
2[X-3(X-)+2]=2(X-4)
2[X-3(X-1)+2]=(2(X)+2(-4))
2[X-36(X-1)+2]=(2X-8)
2[X-3(X-1)+2]=2X-8
2(X+(-3(X)-3(1))+2=2x-8
2(x(-3x+3)+2)=2x+-8
29x+(-3x+3)+2)=2x-82-2x+3+2)=2x-8
2(-2x+5=2x-8
(2(-2)+29-5))=2-8
(-4x+10)=2x-8
-4x+10=2x-8
-4x+10-2x=-8
-6x+10-8
-6x=-10-8-6x+10=-8+-6x=10-8
-6x18
-6x/-6=-18/-
x=-18/-6
x=3
thanked the writer.
2(x-1)+3=3^2x+2
thanked the writer.
Solve for x
1+2x
thanked the writer.
2x-8=2[x-3x+3+2]
2x-8=2[-2x+5]
2x-8=-4x+10
6x=18
x=18/6
x=3
thanked the writer. 